A novel approach to in-situ produce functionally graded silicon matrix composite materials by selective laser melting. (15th July 2017) - Kang, Nan; Coddet, Pierre; Wang, Jiang; Yuan, Hao; Ren, Zhongming; Liao, Hanlin; Coddet, Christian
Abstract: In this work, a functionally graded silicon matrix composite material was in - situ manufactured by a self-developed Magnetic Field assisted Selective Laser Melting (MF-SLM) system free of cracks. A mixture of powders in proportion 50% Al, 50% Si (wt.%) was employed and processed, the build zone being submitted to a static magnetic field provided by permanent magnets. Directional solidification of the primary silicon phase occurs according to the magnetic field direction, due to thermoelectric magnetic convection. In addition, the Si content of the fabricated alloy also evolves (increases) in proportion with the intensity of the SMF, which causes a graded composition and microstructure. Microhardness measurements and ball on disc wear tests were performed for a preliminary assessment of the mechanical properties of the corresponding alloys.